2019
DOI: 10.1097/aog.0000000000003279
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Death in Utah

Abstract: has been reviewed by the Editorial Board and by special expert referees. Although it is judged not acceptable for publication in Obstetrics & Gynecology in its present form, we would be willing to give further consideration to a revised version. If you wish to consider revising your manuscript, you will first need to study carefully the enclosed reports submitted by the referees and editors. Each point raised requires a response, by either revising your manuscript or making a clear and convincing argument as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 21 publications
2
49
0
Order By: Relevance
“…For example, from 2005 to 2014 in Utah, 26% of pregnancy-associated deaths were drug related. 48 In Maryland, the 2019 Annual Report of the Maternal Mortality Review Committee showed that 38% of pregnancy-associated deaths resulted from substance use and unintentional overdose, and for five consecutive years (2012–2017), unintentional drug overdose was the leading cause of pregnancy-associated death. 49 In a recent review from 2007 to 2016 in the 22 states that had adopted the pregnancy checkbox on death certificates, it was found that pregnancy-associated mortality involving opioids more than doubled in terms of both the rate (1.3–4.2/100,000 live births) and the percentage of all pregnancy-associated deaths (4%–10%).…”
Section: Drug Overdose During Pregnancy and Pregnancy-associated Deatmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, from 2005 to 2014 in Utah, 26% of pregnancy-associated deaths were drug related. 48 In Maryland, the 2019 Annual Report of the Maternal Mortality Review Committee showed that 38% of pregnancy-associated deaths resulted from substance use and unintentional overdose, and for five consecutive years (2012–2017), unintentional drug overdose was the leading cause of pregnancy-associated death. 49 In a recent review from 2007 to 2016 in the 22 states that had adopted the pregnancy checkbox on death certificates, it was found that pregnancy-associated mortality involving opioids more than doubled in terms of both the rate (1.3–4.2/100,000 live births) and the percentage of all pregnancy-associated deaths (4%–10%).…”
Section: Drug Overdose During Pregnancy and Pregnancy-associated Deatmentioning
confidence: 99%
“…Having an unrecognized SUD or not receiving medication for an opioid use disorder (OUD) contributes to pregnancy drug-induced overdose deaths. 48 , 51 Despite the evidence that comprehensive pharmacotherapy ( e.g. , methadone, buprenorphine treatment) is the current standard of care for treating OUD during pregnancy and an effective way to prevent opioid overdose in the general population, nearly half of pregnant women with OUD who are receiving treatment in publicly funded centers in the United States are not receiving these medications.…”
Section: Drug Overdose During Pregnancy and Pregnancy-associated Deatmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United States, opioid‐related overdose events are increasingly implicated in pregnancy‐associated deaths, defined as deaths occurring during or within a year of the end of pregnancy, contributing to 11–25% of deaths in several states . The majority of the reported deaths occur later in the postpartum period; in Massachusetts, more than 90% of substance use‐related pregnancy‐associated deaths occurred after 6 weeks postpartum, compared with 60% of all other pregnancy‐associated deaths .…”
Section: Introductionmentioning
confidence: 99%